Bidirectional role of neutrophils in tumor development - Haoxin Luyang; Feng Zeng; Yan Lei; Qian He; Yanhong Zhou; Juan Xu (Molecular Cancer)
Abstract Neutrophils, traditionally considered as non-specific components of the innate immune system, have garnered considerable research interest due to their dual roles in both promoting and inhibiting tumor progression. This paper seeks to clarify the specific mechanisms by which neutrophils play a bidirectional role in tumor immunity and the factors that influence these roles. By conducting a comprehensive analysis and synthesis of a vast array of relevant literature, it has become evident that neutrophils can influence tumor development and invasive migration through various mechanisms, thereby exerting their anti-tumor effects. Conversely, they can also facilitate tumorigenesis and proliferation, as well as affect the normal physiological functions of other immune cells, thus exerting pro-tumor effects. Moreover, neutrophils are influenced by tumor cells and their unique microenvironment, which in turn affects their heterogeneity and plasticity. Neutrophils interact with tumor cells to regulate various aspects of their life activities precisely. This paper also identifies unresolved issues in the research concerning the bidirectional role of neutrophils in tumorigenesis and tumor development, offering new opportunities and challenges for advancing our understanding. This, in turn, can aid in the proper application of these insights to clinical treatment strategies.